(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The political & sociology role of women as a subjectfor research is of recent origin in India. It is significant that there are sofew studies of women’s role in the nationalist movement or of the implicationssocial or political-of their momentous entry into the public sphere. Importantworks on the national movement mostly fail to examine the significance ofwomen’s participation in the struggles.2 Analysis in this area so far hasreceived insufficient attention in histories of India both before and after1975 when the need to study women’s role in history began to be acknowledgedworld-wide. One searches in vain for an adequate study of women’s participationin nationalist historiography. In India as in the rest of the world there areintensive studies underway on the subject of women’s education giving attentionto its necessity and importance. In this study that was conducted for thepurpose of determining the opinions of women, the actual people affected bythis subject, about the necessity of women’s education, it was determined thatthe factors of educational level, age and employment status were allinfluential.